Tracking of the broadbill swordfish, Xiphias gladius, in the central and eastern North Atlantic - Abascal, Francisco Javier; Mejuto-García, Jaime; Quintans, Manolo; Ramos-Cartelle, Ana (Fisheries Research, 2015)
A total of 21 swordfish, Xiphias gladius, were tagged with pop-up satellite tags in northern and southeastern areas of the North Atlantic Ocean. There were seasonal patterns in the horizontal movements, with fish tagged in the central North Atlantic moving southwards from the end of the year, generally south of 25◦N, and returning to the temperate foraging grounds, north of 40◦N, in spring. Although movements mainly took place latitudinally, fish tracks showed connectivity between the north central, north western, south eastern and north eastern North Atlantic. Average estimated daily displacements were 24.7±19.5 km day−1, and could average up to ∼100 km day−1 in some months. The longest track recorded totaled more than 10,000 km. Swordfish showed remarkable physiological versatility, inhabiting waters with SSTs ranging from 10.1 to 28.6 ◦C, and subject to environmental temperatures of c. 4 ◦C–28◦ C, with daily ranges frequently over 15 ◦C (mean 9.2 ± 5.7). Fish showed a clear diel pattern in vertical behavior, feeding at 300–600 m deep during daytime and staying in the mixed layer at night. There was a significant relationship between nocturnal depth and moonphase, quarter and sea surface temperature. The results of the present study are in agreement with the current separation between North Atlantic, Mediterranean and South Atlantic stocks, but suggest that the assumption of a single homogeneous stock in the North Atlantic might be overly simplistic. Further tagging studies, with special emphasis in areas and seasons not covered so far and in combination with other techniques, are still needed to elucidate the uncertainties of Atlantic swordfish stock structure. SI